Consensus guidelines and recommendations for the management and response assessment of chimeric antigen receptor T-cell therapy in clinical practice for relapsed and refractory multiple myeloma: a report from the International Myeloma Working Group Immunotherapy Committee - Lin, Yi; Qiu, Lugui; Usmani, Saad; Joo, Chng Wee; Costa, Luciano; Derman, Benjamin; Du, Juan; Einsele, Hermann; Fernandez de Larrea, Carlos; Hajek, Roman; Ho, P Joy; Kastritis, Efstathios; et al. (The Lancet. Oncology, 2024)
Chimeric antigen receptor (CAR) T-cell therapy has shown promise in patients with late-line refractory multiple myeloma, with response rates ranging from 73 to 98%. To date, three products have been approved: Idecabtagene vicleucel (ide-cel) and ciltacabtagene autoleucel (cilta-cel), which are approved by the US Food and Drug Administration, the European Medicines Agency, Health Canada (ide-cel only), and Brazil ANVISA (cilta-cel only); and equecabtagene autoleucel (eque-cel), which was approved by the Chinese National Medical Products Administration. CAR T-cell therapy is different from previous anti-myeloma therapeutics with unique toxic effects that require distinct mitigation strategies. Thus, a panel of experts from the International Myeloma Working Group was assembled to provide guidance for clinical use of CAR T-cell therapy in myeloma. This consensus opinion is from experts in the field of haematopoietic cell transplantation, cell therapy, and multiple myeloma therapeutics.
Keywords: Multiple Myeloma; mnohočetný myelom; Immunotherapy, Adoptive; konsensus; Receptors, Antigen, T-Cell; chimerické antigenní receptory; Receptors, Chimeric Antigen; Humans; výsledek terapie; imunoterapie adoptivní; Consensus; receptory antigenů T-buněk; lidé; Treatment Outcome